Efeitos do ciclamato de sódio e do aspartame na placenta de uma ratas: estudo morfométrico - Matos, Marcelo Alexandre de (2008)
To evaluate the effects on the placenta of the administration to rats during embryogenesis, of sodium cyclamate or aspartame. Method: Administration of respectively, 14 mg/kg of aspartame via an orogastric sound to a group of rats during their tenth to fourteenth day of pregnancy, of 60 mg/Kg of sodium cyclamate intraperitonially to another group, and of equivalent volumes of saline by the same routes to controls. On the twentieth day of pregnancy five foetuses of each group were aleatorily selected for study. Karyometry was used to evaluate nuclear parameters of the decidua, spongy layers and chorionic villi of the placenta. Results: Weights of foetuses and placentas, as well as lengths of umbilical cords were lower in treated rats, compared to control. While no changes were observed in the decidual layer of the cyclamate-treated group, this layer was altered by aspartame treatment. Nuclear parameters in the spongy layer and chorionic villi were altered in both, cyclamate and aspartame-treated groups. Conclusions: The study numerically demonstrated placenta intoxication by sodium cyclamate or aspartame, and consequent repercussion on foetuses of the use of these substances during pregnancy.